Evaluation of fatigue properties under four-point bending and fatigue crack propagation in austenitic stainless steel with a bimodal harmonic structure - Shoichi Kikuchi; Yuta Nakatsuka; Yoshikazu Nakai; Masashi Natakani; Mie Ota Kawabata; Kei Ameyama (Fracture and Structural Integrity)
Austenitic stainless steel (JIS-SUS304L) with a bimodal harmonic structure, which is defined as a coarse-grained structure surrounded by a network of fine grains, was fabricated using powder metallurgy to improve both the strength and ductility. Four-point bending fatigue tests and K-decreasing tests were conducted in air at room temperature under a stress ratio R of 0.1 to investigate fatigue crack propagation in SUS304L. The fatigue limit of this harmonic-structured material is higher than that of the material with a homogeneous coarse-grained structure. This is attributable to the formation of fine grains by mechanical milling and to the suppression of pore formation. In contrast, the threshold stress intensity range, ?Kth, for the harmonic-structured material is lower than that for the homogeneous coarse-grained material, while the crack growth rates, da/dN, are higher at comparable ?K. These results can be attributed to a reduction in the effective threshold stress intensity range, ?Keff,th, due to the presence of fine grains in the harmonic structure.